Determinants of Children’s Enrollment in Selected Pre-Schools in Tana Delta Sub County, Tana River County, Kenya - Walakisa, Ntondwe, R. (International Journal of Humanity and Social Sciences, 2024)
Purpose: The purpose of the Study is to gather useful information on the determinants of children's enrollment in pre-schools, the study was guided by the following research question "How do parents' attitudes towards pre-school education influence pre-school enrollment?" Literature was reviewed under the following sub heading; parents' attitude towards early learning and pre-school enrollment. Methodology: The researcher employed use of survey method to gather data, simple random was used in sampling respondents. Findings: The study found out that Parents' Attitude towards Pre-School influences children's enrolment as majority (75%) of the parents in the study indicated that pre-school education was important to the child. This shows that majority of parents had a positive perception of pre-school education. Unique Contribution to Theory, Policy and Practice: The researcher recommended that the government should include pre-schools into free primary education and financially support the school feeing program. The County Director of Education Mr M ashengu was a worried person in the declining enrolment of early learners, a view shared by the Director of Preschools, Tana-River County, Mr Abdi Bantta that that the two provided excellent support in solving the puzzle and delve into ways that will significantly reduce the costs incurred by parents' thereby encouraging increased enrollment.